THE ECONOMIC AND ENVIRONMENTAL EFFICIENCY OF AGRIVOLTAIC SYSTEMS IN UZBEKISTAN’S AGRICULTURAL SECTOR (Marketing Journal, 2026)
The growing pressure on agricultural resources, rising energy demand, and intensifying climate impacts have compelled many countries to consider innovative dual-use land technologies. Among these, agrivoltaic systems —allowing simultaneous agricultural prod uction and photovoltaic (PV) electricity generation —emerge as a promising strategic direction. For Uzbekistan, where agriculture remains a core pillar of the economy and solar energy resources are among the richest worldwide, agrivoltaics presents a long -term solution linking green growth, energy independence, and environmental sustainability. This paper examines the economic and environmental efficiency of agrivoltaic systems in Uzbekistan using a conceptual approach, without quantitative modeling. The analysis focuses on land -use optimization, farm -level energy security, climate resilience, mi croclimate benefits, carbon reduction potential, and water -use efficiency. It also identifies institutional, financial, and infrastructural barriers hindering broad implementation. The study concludes with policy recommendations for enabling agrivoltaics t o support national goals outlined in the "Uzbekistan -2030" Strategy, the transition to a green economy, and the modernization of the agricultural sector.
Keywords: agrivoltaics; dual -use land; green economy; renewable energy; sustainable agriculture; Uzbekistan; photovoltaic systems